Peran Kompetensi Profesional Guru dalam Pendidikan Karakter di Era Modernisasi untuk Siswa Sekolah Dasar - Nurbaity, Ajeung Laras; Ahyati, Auli Ihza; Rizqiyah, Nayla; Rendiyawati, Rindi; Agustin, Serlina (Instructional Development Journal, 2024)
The development of education in the modernization era must coincide with the ability of various parties, including parents and teachers to jointly shape the character of children. Character education for children has a function as a provision for the future in facing modern life. Based on the initial observations that have been made by researchers, that seeing the conditions of the development of modernization that affect students' lives, among others, influences the shape of the character of the students themselves. The lack of instilling student character education in elementary schools underlies this research. Then, what is the role and application of teacher professional competence in character education in the modernization era for elementary school students. The research method used in this research is qualitative. Research that focuses on the most important aspects of an object. It involves understanding and exploring phenomena. Based on the presentation of the description it can be concluded that the teacher's professional competence in character building is an important factor that influences the achievement of a learning objective.